Dispersion as a Measure of Rainfall Variability in the Wet Zone of Sri Lanka - Ranasinghe, E.M.S (My University, 2013)
The present study is focused on the variability of annual rainfall in the Wet Zone of Sri Lanka (hereafter referred to as Wet Zone) in the period 1941-2000. A comparative study of two averaging periods 1941-1970 (referred to as 1st 30-year period) and 1971-2000 (referred to as 2nd 30-year period) was carried out. The Wet Zone of Sri Lanka occupies 23 percent of the land area in the country. The Wet Zone has a unique place in the wider geography of Sri Lanka in terms of its physical geography, as well as its human geography. Rainfall in particular, as reflected in landforms, drainage, natural vegetation, economic activities, settlement patterns, and general social fabric and life style of the people. The Wet Zone is the economic power-house and the main area of population concentration in the country and eighty three percent of the land area in the Wet Zone is available for use. With this brief farmable, it is important to analyze the rainfall variability in the Wet Zone. Therefore, dispersion technique has been applied for the analysis of variability of rainfall for the present study. Only 36 out of 182 rainfall-reporting stations in the Wet Zone have selected for the present study (See table. 1)